Narrowing the field: cancer-specific promoters for mitochondrially-targeted p53-BH3 fusion gene therapy in ovarian cancer - Katherine Redd Bowman; Ji Hoon Kim; Carol S. Lim (BMC, 2019)
Abstract Background Despite years of research, the treatment options and mortality rate for ovarian cancer remain relatively stagnant. Resistance to chemotherapy and high heterogeneity in mutations contribute to ovarian cancer's lethality, including many mutations in tumor suppressor p53. Though wild type p53 gene therapy clinical trials failed in ovarian cancer, mitochondrially-targeted p53 fusion constructs, including a fusion with pro-apoptotic protein Bad, have shown much higher apoptotic potential than wild type p53 in vitro. Due to the inherent toxicities of mitochondrial apoptosis, cancer-specificity for the p53 fusion constructs must be developed. Cancer-specific promoters such as hTERT, hTC, Brms1, and Ran have shown promise in ovarian cancer. Results Of five different lengths of hTERT promoter, the − 279/+ 5 length relative to the transcription start site showed the highest activity across a panel of ovarian cancer cells. In addition to − 279/+ 5, promoters hTC (an hTERT/CMV promoter hybrid), Brms1, and Ran were tested as drivers of mitochondrially-targeted p53-Bad and p53-Bad* fusion gene therapy constructs. p53-Bad* displayed cancer-specific killing in all ovarian cancer cell lines when driven by hTC, − 279/+ 5, or Brms1. Conclusions Cancer-specific promoters hTC, − 279/+ 5, and Brms1 all display promise in driving p53-Bad* gene therapy for treatment of ovarian cancer and should be moved forward into in vivo studies. -279/+ 5 displays lower expression levels in fewer cells, but greater cancer specificity, rendering it most useful for gene therapeutics with high toxicity to normal cells. hTC and Brms1 show higher transfection and expression levels with some cancer specificity, making them ideal for lowering toxicity in order to increase dose without as much of a reduction in the number of cancer cells expressing the gene construct. Having a variety of promoters available means that patient genetic testing can aid in choosing a promoter, thereby increasing cancer-specificity and giving patients with ovarian cancer a greater chance at survival.